2022
DOI: 10.1136/jim-2021-002314
|View full text |Cite
|
Sign up to set email alerts
|

MHR and NHR but not LHR were associated with coronary artery disease in patients with chest pain with controlled LDL-C

Abstract: Several leukocyte to high-density lipoprotein cholesterol (HDL-C) ratios, including monocyte to HDL-C ratio (MHR), neutrophil to HDL-C ratio (NHR) and lymphocyte to HDL-C ratio (LHR), have been proposed as novel inflammatory indicators. We performed a cross-sectional study to investigate the relationships between these leukocyte to HDL-C ratios and coronary artery disease (CAD) in patients with chest pain with controlled low-density lipoprotein cholesterol (LDL-C). A total of 3482 patients with chest pain with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In our study, MHR showed significant differences between CAD and non-CAD groups, and it remained a risk factor for CAD based on multifactor regression analysis. Liu et al also demonstrated that a higher MHR is a risk factor for severe stenosis, and even though patients with chest pain have achieved LDL-C < 1.8 mmol/l, MHR maintained their predictive abilities and remained associated with the occurrence and severity of CAD [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, MHR showed significant differences between CAD and non-CAD groups, and it remained a risk factor for CAD based on multifactor regression analysis. Liu et al also demonstrated that a higher MHR is a risk factor for severe stenosis, and even though patients with chest pain have achieved LDL-C < 1.8 mmol/l, MHR maintained their predictive abilities and remained associated with the occurrence and severity of CAD [22].…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al . also demonstrated that a higher MHR is a risk factor for severe stenosis, and even though patients with chest pain have achieved LDL-C < 1.8 mmol/l, MHR maintained their predictive abilities and remained associated with the occurrence and severity of CAD [ 22 ]. Our study also examined the diagnostic value of MHR: When the cutoff value of MHR was set to 0.47, the prediction ability for CAD was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Lamichhane P et al [ 44 ] have demonstrated that NHR can be used for risk stratification and for predicting short-term and long-term prognoses in clinical cardiovascular diseases. Additionally, Liu M et al [ 45 ] identified an independent correlation between NHR and coronary heart disease and severe stenosis in patients presenting with chest pain. NHR also showed comparable predictive value for severe coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data on MHR in CVD in male patients are limited, and they describe a higher MHR in men with CCS [9,10]. Furthermore, this marker was shown to be an independent predictor of CCS diagnosis [11,12] and progression [9,13,14]. Higher MHR was also observed in patients with acute coronary syndrome (ACS) [15][16][17], stent embolus in patients with ACS treated with percutaneous coronary intervention [18], and microvascular angina [19].…”
Section: Introductionmentioning
confidence: 99%